Perancangan dan Pembuatan Sistem Informasi Peminjaman dan Pengembalian Dokumen Rekam Medis Rawat Jalan di RSF Mangusada Badung - Nur Malika Jamil; Sustin Farlinda; Atma Deharja (Politeknik Negeri Jember, 2020)
Registration of loans and refunds of medical records at RSD Mangusda Badung still there is an obstacle that is the loan and refunds data of medical records in the period of 1x24 hours hours is not complete and, there is no description of loan and return timeÂ of medical record documents in the expedition. This research aims to design and create information system for loans and refunds theÂ medical records by using waterfall method at RSD Mangusada Badung. This research was conducted in RSD Mangusada Badung. The method of this research used is a qualitative method with the waterfall system development method. The data collection methods used are interviews, observations and documentation. The result of this research is the design and creation of a loan information system for the return of medical record documents using waterfall method is expected to facilitate the officer filing at Puskesmas Banjarsengon to do their duties.